Boganmeldelser - Hauge, Ragnar; Kyvsgaard, Britta; Carstensen, Gitte; Olausson, Leif Petter; Jareborg, Nils; Koch, Henning; Koch, Ida; Lauridsen, Preben Stuer; Vestergaard, Jørn; Johanson, Eva; Lodberg, Poul; Gammeltoft-Hansen, Hans (Nordisk Tidsskrift for Kriminalvidenskab, 1985)
Book reviews